Review of Shikonin and Derivatives: Isolation, Chemistry, Biosynthesis, Pharmacology and Toxicology - Yadav, Snehlata; Sharma, Ajay; Nayik, Gulzar Ahmad; Cooper, Raymond; Bhardwaj, Garima; Sohal, Harvinder Singh; Mutreja, Vishal; Kaur, Ramandeep; Areche, Franklin Ore; AlOudat, Mohannad; Shaikh, Ayaz Mukarram; Kovács, Béla; et al. (Frontiers in Pharmacology, 2022)
Shikonin and its derivatives, isolated from traditional medicinal plant species of the genus Lithospermum, Alkanna, Arnebia, Anchusa, Onosma, and Echium belonging to the Boraginaceae family, have numerous applications in foods, cosmetics, and textiles. Shikonin, a potent bioactive red pigment, has been used in traditional medicinal systems to cure various ailments and is well known for its diverse pharmacological potential such as anticancer, antithrombotic, neuroprotective, antidiabetic, antiviral, anti-inflammatory, anti-gonadotropic, antioxidants, antimicrobial and insecticidal. Herein, updated research on the natural sources, pharmacology, toxicity studies, and various patents filed worldwide related to shikonin and approaches to shikonin's biogenic and chemical synthesis are reviewed. Furthermore, recent studies to establish reliable production systems to meet market demand, functional identification, and future clinical development of shikonin and its derivatives against various diseases are presented.